STEM ISCIT Learning Tools to Improve Integrative Scientific Thinking - Dian Artha Kusumaningtyas; Dwi Sulisworo; Jumadi; Edi Istiyono (Indonesian Review of Physics (IRiP), 2021)
Learning in the era of the new university regulations experienced a revolution in students’ learning style and teachers’ teaching style because this situation caused many changes in the learning system. Different types of learning alternatives are carried out to achieve learning that meets these conditions. Integrative STEM was selected as one of the learning models in the new order era. However, inclusive STEM learning is difficult to do without support or learning tools, especially in distance learning. Based on these needs, this research was carried out to develop support devices for the integrative STEM model in university physics class students. This research is research and development (R&D). The development model used uses a 4D development model. The 4D model is synonymous with definition, design, development, and dissemination. In this study, an assistive device model was developed in an integrative MINT learning device. The analysis results show that the development of integrative learning tools based on STEM for students is rated as good, with an average of 80%.